Ophthalmic artery changes in type 2 diabetes with and without acute coronary syndrome - Wu, Lan-ting; Wang, Jia-lin; Wang, Yan-ling (Journal of translational medicine, 2022)
Ocular blood flow provides a new perspective for studying the effects of diabetes and ischemic heart disease on systemic blood flow, pathological mechanisms, and prognosis. Previous studies have analyzed the hemodynamic changes of the ophthalmic artery (OA) in patients with diabetes and ischemic heart disease, but the results remain controversial due to limited observation methods. We aimed to explore the morphological and hemodynamic features in the OA in patients with type 2 diabetes (T2D) with and without acute coronary syndrome (ACS). In total, 134 participants, including 30 control participants, 34 with ACS only, 34 with T2D only, and 36 with both ACS and T2D, undergoing computed tomography angiography were enrolled. Three-dimensional OA models were reconstructed, and morphological parameters of the OA were measured. In addition, numerical simulations using computational fluid dynamics were used to acquire hemodynamic parameters of the OA. In this study, 134 OA models were reconstructed. Morphological measurements revealed a smaller initial OA diameter in the T2D group than in the other two ACS groups. A hemodynamic simulation showed a significantly lower OA blood velocity in patients with ACS and T2D than that in controls (P < 0.001). The mass flow ratios in all disease groups were lower than those in the control group (P < 0.001, P = 0.020, and P < 0.001, respectively). The ACS and T2D groups had higher OA pressure levels than those of the control group (P = 0.013). The OA blood velocity and mass flow ratio were correlated with several clinical parameters. This study revealed morphological and hemodynamic differences in the OA between patients with T2D with and without ACS. Furthermore, the hemodynamic characteristics of the OA correlated with clinical prognostic biomarkers, suggesting the potential predictive ability of the OA.